Microwave hydrothermal-reduction synthesis of zanthoxylum trunk-like Co/CoAl2O4/sepiolite nanocomposite. Issue 4 (15th February 2021) - Hao, Ming; Gao, Peizhang; Liu, Wei; Fang, Baizeng; Liang, Jinsheng; Zhang, Tingting; Ding, Youpeng; Zhang, Hui; Wang, Fei
Abstract: In this work, a novel Co/CoAl2 O4 /sepiolite nanocomposite was synthesized by reducing the CoAl2 O4 /sepiolite nanocomposite prepared via a microwave hydrothermal method. The effects of the content of sepiolite, types of the organic matters used, and their dosage on the microstructure of the CoAl2 O4 /sepiolite nanocomposite were investigated and the optimal conditions for fabricating the CoAl2 O4 /sepiolite nanocomposite were identified. Subsequently, the influence of the reduction temperature on the microstructure of the Co/CoAl2 O4 /sepiolite nanocomposite was studied. According to the various surface characterizations, the sample synthesized under the optimal conditions (i.e., with 10 vol% triethanolamine and 10 wt% sepiolite followed by the reduction at 650 °C for 3 h) showed spherical CoAl2 O4 evenly dispersed on sepiolite nanofibers along with fine cobalt nanoparticles embedded on the surface of CoAl2 O4 . As a model reaction, Fischer-Tropsch synthesis was examined with the as-synthesized materials. The optimal sample has demonstrated a higher selectivity for C5+ (high-carbon hydrocarbons) and lower selectivity for CO2, CH4, and C2 –C4 compared with the control sample. This work is believed to provide an effective strategy for low-cost batch fabrication of highly efficient supported cobalt-based catalysts with a novel transition layer where fine Co nanoparticles can be anchored with good dispersion.